Mitologi Religius dan Toleransi Orang Jawa: Telaah Pemikiran Benedict Anderson - Roibin, Roibin (el Harakah: Jurnal Budaya Islam, 2008)
The national revolution has brought effects on many aspects including the changing process of Javanese syncretism and relativism into the tolerance of Javanese. Anderson argues that Javanese relativism should not be understood as the tolerance toward public differences by ignoring races, colors, and beliefs. In fact, Javanese relativism does not bring any effect on other ethical groups in Indonesia. Therefore, the idea of openness and tolerance which has been admired from Javanese value is just like chauvinism cultural terminology. Javanese cultural behavior still becomes a mystery as its practice of tolerance measured by the wish and propinquity to its culture. The term of tolerance which becomes a pride and an ideology for Javanese people, in fact, shows the opposite situation as the practices of religiousness are still measured by social hierarchy. This character is inseparable from what is called a rigid religious mythology. It, then, offers much particular morale structure with diverse forms. Revolusi nasional telah membawa dampak pada banyak aspek termasuk perubahan proses sinkretisme dan relativisme Jawa menjadi toleransi orang Jawa. Anderson berpendapat bahwa relativisme Jawa tidak boleh dipahami sebagai toleransi terhadap perbedaan publik dengan mengabaikan ras, warna, dan kepercayaan. Kenyataannya, relativisme Jawa tidak membawa dampak pada kelompok etis lain di Indonesia. Oleh karena itu, gagasan keterbukaan dan toleransi yang dikagumi dari nilai Jawa sama seperti istilah budaya chauvinisme. Perilaku budaya Jawa masih menjadi misteri karena praktik toleransinya diukur dengan harapan dan propimquity terhadap budayanya. Istilah toleransi yang menjadi sebuah kebanggaan dan ideologi bagi orang Jawa, pada kenyataannya, menunjukkan situasi yang berlawanan karena praktik religiusitas masih diukur dengan hierarki sosial. Karakter ini tak terpisahkan dari apa yang disebut mitologi religius yang kaku. Kemudian, ia menawarkan banyak struktur moral tertentu dengan beragam bentuk.